Effects of Thermocycling on the Retention of Various Cements of One-Unit and Three-Unit Fixed Implant-Supported Restorations - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2012)
Purpose: To investigate the physical retention of different cements on one-unit and three-unit implant-supported restorations before and after thermocycling. Materials and Methods: Twenty acrylic resin maxilla models with a single missing tooth and three missing teeth were fabricated and implants were placed. Cast partial denture copings were cemented to Straumann solid abutments with seven different cements. Specimens were placed in a humidifier at 37 degrees C for 24 hours; half of them were then subjected to thermocycling. The tensile force was measured using a universal testing machine with a crosshead speed of 0.5 mm/min. The retention force required to remove the specimens was recorded and the data were submitted to statistical analyses. Results: The retentive strength of the cements was highest for Multilink Implant, followed in descending order by Kavitan Cem, Adhesor Carbofine, Premier Implant, Adhesor, RelyX Temp, and Cavex before and after thermocycling for both one- and three-unit restorations. The bond strength was statistically significantly higher for three-unit than for one-unit restorations before and after thermocycling, and there were statistically significant differences between cements for all groups before and after thermocycling. Both groups showed a statistically significant decrease in bond strength after thermocycling, and the largest differences were seen for Cavex and RelyX Temp for one-unit restorations and Cavex, RelyX Temp, and Kavitan Cem for three-unit restorations. Conclusions: The bond strength value was higher for three-unit than for one-unit restorations, and thermocycling reduced the bond strength of cements, especially Cavex, RelyX Temp, and Kavitan Cem. INT J ORAL MAXILLOFAC IMPLANTS 2012;27:567-576.
Keywords: cement retention; dental implants; implant-supported restorations; thermocycling; PROVISIONAL LUTING AGENTS; CROWN RETENTION; SURFACE-ROUGHNESS; BOND STRENGTH; SYSTEM; ABUTMENTS; RECEMENTATION; MULTICENTER; RESISTANCE